Taxpayers' perceptions on tax evasion behaviour: an empirical study in Malaysia. Issue 3 (8th May 2017) - Pui Yee, Chan; Moorthy, Krishna; Choo Keng Soon, William
Abstract : Purpose: The success of self-assessment tax system is voluntary compliance with the tax laws. When tax evasion is seen as unacceptable, taxpayers will tend to evade tax less. Hence, the understanding of taxpayers' attitude on tax morality towards a tax system has to be enhanced to minimize tax evasion cases. The purposes of this study are to examine the relationship between tax fairness, tax knowledge, enforcement level and social exchange towards taxpayers' attitude of tax morality under the self-assessment system in Malaysia and also to identify the relationship between taxpayers' attitude of tax morality and taxpayers' perceptions on tax evasion. Design/methodology/approach: Data were collected from 400 taxpayers through a questionnaire and analysed. Findings: From the analysis, it has been found out that tax knowledge is the most important tax system characteristic that affects taxpayers' attitude of tax morality. In addition, taxpayers' attitude of tax morality is significant to taxpayers' perceptions on tax evasion in Malaysia. Originality/value: The findings of this study would be useful for the government to further improve the present tax system to increase voluntary tax compliance.